Recent progress in the development of near-infrared organic photothermal and photodynamic nanotherapeutics - Zhu, Houjuan (2019)
Phototherapies including photothermal therapy (PTT) and photodynamic therapy (PDT) have gained considerable attention due to their high tumor ablation efficiency, excellent spatial resolution and minimal side effects on normal tissue. In contrast to inorganic nanoparticles, near-infrared (NIR) absorbing organic nanoparticles bypass the issue of metal-ion induced toxicity and thus are generally considered to be more biocompatible. Moreover, with the guidance of different kinds of imaging methods, the efficacy of cancer phototherapy based on organic nanoparticles has shown to be optimizable. In this review, we summarize the synthesis and application of NIR-absorbing organic nanoparticles as phototherapeutic nanoagents for cancer phototherapy. The chemistry, optical properties and therapeutic efficacies of organic nanoparticles are firstly described. Their phototherapy applications are then surveyed in terms of therapeutic modalities, which include PTT, PDT and PTT/PDT combined therapy. Finally, the present challenges and potential of imaging guided PTT/PDT are discussed.